THE POLITICS OF INTERNET FREEDOM RANKINGS: A CALL FOR A COMPARATIVE FRAMEWORK FOR ASSESSING INTERNET FREEDOM - Wijermars, Mariëlle; Lokot, Tetyana (AoIR Selected Papers of Internet Research, 2020)
This paper critically assesses current regimes of internet governance and the role of internet freedom rankings therein. In particular, it aims to initiate a debate ultimately leading to the development of a ground-breaking comparative framework for assessing internet policy, departing from the assumption that current frameworks for measuring internet freedom are predicated too strictly on the dichotomy of democracy/non-democracy. Most stakeholders involved in benchmarking internet freedom approach it from a Western-leaning perspective that uncritically assumes that democracy-related practices are embedded in the very origins of the internet and therefore, the levels of democratisation can serve as valid indicators of internet freedom. As a result, these frameworks lack when applied to invasive policies and public administration practices implemented in democracies, while lacking when applied to policies and practices in non-democracies. The conceptualization and operationalization of the concept of internet freedom that underlies internet freedom rankings is of particular importance since the promotion of internet freedom is an integral part of foreign policy and rankings serve as a source of information and justification for prioritizing funding and efforts. Rankings can also impact states’ reputations, serve as advocacy tools in public diplomacy, but also impede justified criticism aimed at states who score well on key indicators. Through this intervention piece, we aim to initiate debate on developing an alternative framework for assessing internet policy. Shifting attention away from the singular focus on regime kind and politics enables us to develop a more complex system of coordinates for assessment.